Fucosterol Causes Small Changes in Lipid Storage and Brassicasterol Affects some Markers of Lipid Metabolism in Atlantic Salmon Hepatocytes. Issue 7 (27th September 2018) - Liland, Nina S.; Pittman, Karin; Whatmore, Paul; Torstensen, Bente E.; Sissener, Nini H.
Abstract: Several feeding trials with Atlantic salmon fed naturally high phytosterol concentrations due to dietary rapeseed oil inclusion have shown changes in lipid metabolism and increased hepatic lipid storage in the fish. An in vitro trial with Atlantic salmon hepatocytes was, therefore, performed to study the possible direct effects of phytosterols on lipid storage and metabolism. The isolated hepatocytes were exposed to seven different sterol treatments and gene expression, as well as lipid accumulation by Oil Red O dyeing, was assessed. Fucosterol, a sterol found in many algae species, had an effect on the size of individual lipid droplets, leading to smaller lipid droplets than in the control without added sterols. A sterol extract from soybean/rapeseed led to an increase in the percentage of hepatocytes with visible lipid droplets at 20× magnification, while hepatocytes of both the sterol extract‐treated groups and fucosterol‐treated groups had a larger proportion of their area covered with lipids compared to control cells. Brassicasterol, a sterol characteristic of rapeseed oil, was the only sterol treatment leading to a change in gene expression, affecting the expression of the nuclear receptors, peroxisome proliferator‐activated receptor gamma ( pparg ) and retinoid X receptor ( rxr ). The current study thus shows that phytosterols can have direct, although subtle, effects on both hepatic lipid storage and gene expression of Atlantic salmon in vitro .